Co substituted BaFe12O19 ceramics with enhanced magnetic resonance behavior and microwave absorption properties in 2.6 – 18 GHz. Issue 11 (1st August 2019) - Feng, Gangli; Zhou, Wancheng; Deng, Hongwei; Chen, Dan; Qing, Yuchang; Wang, Chunhai; Luo, Fa; Zhu, Dongmei; Huang, Zhibin; Zhou, Yingying
Abstract: BaFe12- x Co x O19 (BFCO, x  ≤ 0.4) ceramics with superior magnetic and electromagnetic (EM) properties were prepared using Co 3+ substituted BaFe12 O19 (BFO) in 2.6–18 GHz. Compared with the ceramics without Co 3+, the incorporation of 40 mol% Co 3+ enhances magnetic properties; the saturation magnetization ( M S ) is improved by about 55.6 emu·g −1 due to the variety of magnetocrystalline anisotropy. The resonance behaviors of complex permeability are observed and resonance frequency shifts to lower frequency range from 6 to 3 GHz. The minimum reflection loss ( RL ) of −32.1 dB (<−10 dB) is obtained at 11.2 GHz in 8.5–13.5 GHz at 2.0 mm thickness in the sample with x  = 0.4, which suggests that such ceramics is highly promising as effective microwave absorbers for EM applications.